2010
DOI: 10.1111/j.1468-0432.2009.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

The Business of Caring: Women's Self‐Employment and the Marketization of Care

Abstract: Our goal in this article is to contribute to a differentiated analysis of paid caring work by considering whether and how women's experiences of such work is shaped by their employment status (for example, self-employed versus employee) and the nature of care provided (direct or indirect). Selfemployed care workers have not been widely studied compared with other types of care workers, such as employees providing domestic or childcare in private firms or private homes. Yet their experiences may be quite distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…Entrepreneurs also perceived financial problems as a key stressor in a qualitative study (Lechat & Torrès, 2016). Equally three related studies found consistently that entrepreneurs with low income had lower MWB (Anderson & Hughes, 2010;D'Angelo et al, 2016;Kwon & Sohn, 2017).…”
Section: Personal Motivations and Valuesmentioning
confidence: 87%
“…Entrepreneurs also perceived financial problems as a key stressor in a qualitative study (Lechat & Torrès, 2016). Equally three related studies found consistently that entrepreneurs with low income had lower MWB (Anderson & Hughes, 2010;D'Angelo et al, 2016;Kwon & Sohn, 2017).…”
Section: Personal Motivations and Valuesmentioning
confidence: 87%
“…Qualitative analyses of care work provide rich descriptions of the downward trajectories of highly feminized and racialized populations (who are also disproportionately migrants), often serving elderly, sick, or preschool-aged clients (e.g. Anderson and Hughes, 2010;Geisen and Parreñas, 2013). These women work in hospitals, in the post-acute health-care sector, in daycares or in private homes, and the negative repercussions of their employment conditions are often felt across families and communities.…”
Section: Disaggregating Care Work: High-and Low-status Occupationsmentioning
confidence: 99%
“…England was one of the first European countries to adopt a marketisation policy of care provision combined with a broader agenda of personalisation (Colombo et al, 2011;Himmelweit, 2014). Policy developments, including personalisation and the marketisation of care delivery, have (arguably) led to increased levels of precarious working arrangements, casualisation and job insecurity (Anderson and Hughes, 2010;McGann et al, 2016). Evidence of increased casualisation and fragmentation of care work is significant when considering a sector that continues to rely on 'vulnerable workers', especially women with lower skill levels and migrants (Baines and Cunningham, 2011).…”
Section: Introductionmentioning
confidence: 99%